Analisis Yuridis Restorative Justice Dalam Kepastian Hukum Terhadap Anak Pelaku Tindak Pidana - Annisa Fitri Arrum Melati; Syawaludin; Marsudi Utoyo (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
This study analyzes the application of restorative justice in juvenile crime cases. This approach focuses on resolving crime through the participation of victims, perpetrators, and the community, rather than solely focusing on punishment. Many children commit crimes due to economic and social pressures. Therefore, the law requires the implementation of diversionary measures outside the legal process at every stage of a juvenile case, from investigation to trial. Diversion considers various factors, such as the type of crime, the age of the child, and environmental support. Judges act as facilitators of diversion and have the authority to examine and decide on juvenile cases. The recommendation from this study is the importance of protecting children in the criminal justice system, one of which is by continuing to promote restorative justice through diversion.